Development of pressure system for decellularization of porcine esophagii for organ regeneration - Lim, Ashley Xuan Yu (Nanyang Technological University, 2022)
Advancement in the study of tissue and organ repair and regeneration has resulted in an increase in demand for suitable acellular biological scaffolds from decellularized donor organs. To achieve successful decellularization, the process should be capable of decellularizing complete donor organs while retaining the structural and functional proteins that makes up the extracellular matrix (ECM). This study focused on achieving successful decellularization with minimal resource use. In this study, porcine esophagi were immersed in full thickness with 0.5% w/v Sodium Dodecyl Sulfate solution for up to 7 days. Decellularized porcine esophagi were examined for residual DNA content, and their matrix structure were analyzed via histological examination. The results from this study revealed that full thickness porcine esophagi treated via immersion in an ionic surfactant were decellularized with their structural and biochemical integrity intact in the ECM. Results from histological examination showed that the ECM structure and its fibrous network were retained after decellularization. The residual DNA concentration in decellularized samples were found to be 0.052 ± 0.033 µg/mℓ after 5 days of decellularization, which is significantly lower than the DNA concentration of native samples (1.34 ± 0.22 µg/mℓ).